Peranan Alat Transportasi (Taksi) Dalam Mendukung Industri Pariwisata di Bali - Sadwahyuni, Theresia (Jurnal Bahasa & Pariwisata, 2011)
The role of transportation in developing the tourism industry can not be underestimated. The tourism industry is supported by transportation without the 'well organize' is not likely to experience progression. This is experienced by the tourism industry in Bali. With the development of the tourism industry in Bali, the role of transportation could no longer be separated. Taxi transportation in Bali is growing rapidly. Taxis operating in Bali are over quota. This gives rise to unfair competition. As happened in early 2010, in Bali had been a confusion between the taxi and its driver. As a result of confusion between the taxi fleet in Bali would also affect the development of tourism in Bali. The tourists were afraid to use taxis. One of the efforts undertaken to address problems that occur related to taxi transport is by conducting education and training.